Business environments versus corporate survival in Estonia and Poland in 2001–2009 - Grzegorz Gołębiowski; Piotr Wiśniewski (Contemporary Economics)
Corporate longevity is - in essence - determined by a company's intrinsic competitive advantage (sometimes dubbed a "moat") as well as exogenous factors: from business doing ease - to broader, macroeconomic and strategic factors. In this study, we have endeavoured to compare the business environments and corporate sectors of two recent entrants into the European Union: Estonia and Poland. Overall, Estonia, thanks to greater resolve in post-communist liberal transition, has consistently ensured a superior corporate governance framework. Surprisingly, it is the macroeconomic and strategic steadiness that led to higher corporate survival in Poland. The global economic crisis of 2007-2009 is expected to further back this claim, as the patterns of macroeconomic growth for both countries are set to widen.